A qualitative assessment tool for innovative waste logistics scenarios: A case study for Flanders - Jeffrey Willems; Tom Pauwels; Edwin Van Hassel; Thierry Vanelslander; Steve Sel (Journal of Shipping and Trade (JST), 2022)
With new, innovative logistics tools and frameworks coming to the market rather quickly, developing a decision support framework to assess its value before carrying out extensive, quantitative economic assessment studies and large-scale implementation is necessary. This paper focuses on developing a qualitative decision support framework-aiding the deployment of successful tools in the logistics landscape and avoiding high sunk costs without added value. Resulting in a qualitative tool based on a literature review and industry expert interviews. The derived parameter impact model assesses the importance of different parameters, allowing to find opportunities without the need for extensive information and/or investments. Therefore, the parameter impact model was applied to three different cases of waste logistics located in Flanders: (1) the use of telemetry (i.e., the use of sensors to identify the filling rate of waste collection points remotely), (2) small waste compactors on the business side, and (3) inland waterways to transport waste to treatment centers. The qualitative results can vary depending on the specific case, establishing the fundament for future innovations.
Keywords: 650; Decision support tool; Parameter impact model; Reverse logistics; Waste logistics